Improving EFL students’ speaking skill through academic oral expression tasks at the high school level - Valdivieso-Arcos, Gabriela Soraya; Argudo-Serrano, Juanita Catalina (EPISTEME KOINONIA, 2022)
One of the major concerns of teachers of English as a foreign language (EFL) is to get students to interact in the classroom; in this sense, this study analyzed the perceptions of specific strategies to improve speaking skills used by students at the "Ramona Auxiliadora Marcillo Chica" Educational Unit. A questionnaire was used to collect data, the results showed how students learn English and what strategies they use for this purpose; also, the data analysis indicates levels of commitment, autonomy, and a certain indifference with respect to EFL learning. This leads us to conclude that, students can improve their oral skills as long as English teachers implement effective strategies and methodologies in the classroom, such as reading aloud and the use of songs, which will enable students to improve their oral skills with accuracy and spontaneity.